Flood damage survey and assessment : new insights from research and practice - Molinari, Daniela; Menoni, Scira; Ballio, Francesco (Geophysical monograph ;, 2017)
"Several scholars across the globe identified the present lack of high quality damage data as the main constraint to efficient risk mitigation. The need for a systematic collection of damage data in the aftermath of flood events come into light, thus the aim being the creation of complete and reliable databases. Flood damage data collected in the aftermath of a disastrous event can support a variety of actions, which include: (i) the identification of priorities for intervention during emergencies, (ii) the creation of complete event scenarios on the basis of which understanding the fragilities of the flooded areas and tailoring risk mitigation strategies, (iii) the definition of victims compensation schemes, and (iv) the validation/definition of damage models to feed cost-benefit analysis of structural and non-structural mitigation actions (including insurance schemes). Volume highlights include: A good compilation of real world case studies elaborating on the survey experiences and best practices associated with flood damage data collection, storage and analysis, that can help strategize flood risk mitigation in an efficient manner; Valuable contributions covering different flooding phenomena such as riverine and mountain floods, different spatial level of analysis from local to global scales, and different stakeholders perspectives, e.g. public decision makers, researchers, private companies; and contributions from leading experts in the field, researchers and practitioners, including civil protection actors working at different spatial and administrative level, insurers and professionals working in the field of natural hazards mitigation. Flood Damage Survey and Assessment: New Insights from Research and Practice will be a valuable resource to all earth scientists, hydrologists, meteorologists, geologists, geographers, civil engineers, insurers and policy decision makers"--Publisher's website, November 8, 2017.